2011
DOI: 10.1007/s00198-011-1750-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soy isoflavone on bone mineral density in postmenopausal Taiwanese women with bone loss: a 2-year randomized double-blind placebo-controlled study

Abstract: SummaryThe treatment of 300-mg/day isoflavones (aglycone equivalents) (172.5 mg genistein + 127.5 mg daidzein) for 2 years failed to prevent lumbar spine and total proximal femur bone mineral density (BMD) from declining as compared with the placebo group in a randomized, double-blind, two-arm designed study enrolling 431 postmenopausal women 45–65 years old.IntroductionThis study evaluated the effects of soy isoflavones on bone metabolism in postmenopausal women.MethodsFour hundred and thirty-one women, aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 34 publications
0
58
0
4
Order By: Relevance
“…46,74,75,77 Combined with the biphasic effect of SI, there might be no effect on preserving bone loss in long-term studies when the dose was too high (>200 mg/day). 78,79 According to Table 2, the practical SI dosage for a long-term study among western females might be around 80-120 mg/day.…”
Section: Intervention Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…46,74,75,77 Combined with the biphasic effect of SI, there might be no effect on preserving bone loss in long-term studies when the dose was too high (>200 mg/day). 78,79 According to Table 2, the practical SI dosage for a long-term study among western females might be around 80-120 mg/day.…”
Section: Intervention Materialsmentioning
confidence: 99%
“…Some studies showed significant prevention in bone loss (BMD/BMC) over the duration of the studies 35,46,47,[58][59][60][61][62][63][64][65][66][67][68] ; others did not prove to have significant effects. 18,[69][70][71][72][73][74][75][76][77][78][79] Bone remodeling is a slow process. It normally requires 6-18 months to reach a new equilibrium, and the time required to complete each cycle may be increased with age.…”
Section: Intervention Materialsmentioning
confidence: 99%
“…In contrast, a meta-analysis by Taku et al [ 33 ] that included data on 1,240 menopausal women showed that a dose of 82 mg/day soy iso fl avones signi fi cantly increased spine BMD by 22.25 mg/cm [ 19,21,22 ] , all of which are essentially negative.…”
Section: Meta-analyses Of Randomized Control Trialsmentioning
confidence: 86%
“…In another large 2-year double-blind placebo-controlled study of 431 Chinese postmenopausal women, aged 55-56 years, from Taiwan [ 22 ] , the highest dose yet evaluated of iso fl avones, 300 mg/ day containing 172.5 mg of genistein, was given in the form of three capsules, each with 50 mg taken two times a day; there was no signi fi cant effect on spine and hip BMD. In this study the baseline intake of iso fl avones was high (up to 53 mg/day) and the authors suggested that the high-baseline soy intake could mask the effects of iso fl avones on bone.…”
Section: Intervention Studies Of Soy Iso Fl Avones and Bone Mineral Dmentioning
confidence: 99%
“…However, in the Asian studies, reduced risks were associated with extremely low soy protein intakes, which argue against an increase in IGF-1 contributing to the protection against fracture, and the association with soymilk intake was thought by the authors of this study to be due to the calcium it provided. Most interest in the skeletal benefits of soy is due to its high isoflavone content [69][70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%